The HLA‐B*58:01:20 allele identified in a volunteer donor for hematopoietic stem cell transplant. (1st July 2018) - Baek, I.‐C.; Choi, E.‐J.; Shin, D.‐H.; Kim, H.‐J.; Kim, T.‐G.
Abstract : HLA‐B*58:01:20 differs from HLA‐B*58:01:01:01 by a single synonymous nucleotide exchange at position 297 in exon 3.